Trauma, Civilization, Reproduction. - Tani, Toru (Investigaciones Fenomenológicas, 2012)
On March 11, 2011, a large earthquake struck Japan and was followed by a series of devastating tsunamis. One of these tsunamis triggered an explosion at Fukushima Daiichi Nuclear Power Plant. March 11 was a natural catastrophe (that civilization failed to prevent) on one hand, and a manmade catastrophe (that civilization created and made worse) on the other. The catastrophe was said to be unprecedented and singular. What does it mean to speak/write about a singular event? How did I / we experience this event? A phenomenological analysis leads us to the complex relationship between nature and civilization on one hand, and the problem of trauma experience on the other. A traumatic experience is essentially singular, but it can be reproduced in language, and even more today with the help of (civilization) technology, in visual images that can be recorded, reproduced, repeated, and sent to far corners of the earth. This reproducibility can help us to integrate the trauma within the normal flow of time, but it also conceals from us the root of the trauma and the possibilities of new trauma.